A Latent Class Analysis of Parental Alcohol and Drug Use: Findings from the Avon Longitudinal Study of Parents and Children. (May 2020) - Lowthian, Emily; Moore, Graham; Greene, Giles; Kristensen, Sara Madeleine; Moore, Simon C.
Highlights: We identified four parental substance use classes using quantity-frequency measures. Heavy use of alcohol formed a class which also included a large proportion of drug users. Mothers' and their partner's tended to have similar patterns of substance use behaviours. Abstract: Previous measures of parental substance use have often paid limited attention to the co-occurrence of alcohol and drugs, or to the between-parent dynamics in the use of substances. These shortcomings may have important implications for our understandings of the relationship between parental substance use and child wellbeing. Using data from the Avon Longitudinal Study of Parents and Children, a UK community-based cohort study from 1990 onwards ( n = 9, 451), we identified groups of parental substance use using latent class analysis. The 4-class solution offered the best fit, balancing statistical criteria and theoretical judgement. The results show distinct classes across the range of parental substance use, including very low users, low users, moderate users and heavy users. These classes suggest that substance use patterns among mothers are somewhat mirrored by those of their partners, while heavy use of alcohol by mothers and their partners is related to increased mothers drug use. We suggest that studies that investigate the effects of parental substance use on child wellbeing should pay greater attention to the dynamics of substance use by parental figures.